1992
DOI: 10.1126/science.257.5073.1050
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Drug Resistance: Implications for a Post—Antimicrobial Era

Abstract: In the last several years, the frequency and spectrum of antimicrobial-resistant infections have increased in both the hospital and the community. Certain infections that are essentially untreatable have begun to occur as epidemics both in the developing world and in institutional settings in the United States. The increasing frequency of drug resistance has been attributed to combinations of microbial characteristics, selective pressures of antimicrobial use, and societal and technologic changes that enhance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
655
0
21

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,166 publications
(681 citation statements)
references
References 38 publications
5
655
0
21
Order By: Relevance
“…As mentioned previously, the antibiotic resistance of some bacterial strains has become a serious health problem as resistance to multiple antibiotics has been commonly described (Cohen 1992;Gibbons 1992;Siu 2002;Frontoso et al 2008) and was observed also in our study. Few studies are available on the development of antibiotic resistance of bacteria in horses.…”
Section: Discussionsupporting
confidence: 55%
“…As mentioned previously, the antibiotic resistance of some bacterial strains has become a serious health problem as resistance to multiple antibiotics has been commonly described (Cohen 1992;Gibbons 1992;Siu 2002;Frontoso et al 2008) and was observed also in our study. Few studies are available on the development of antibiotic resistance of bacteria in horses.…”
Section: Discussionsupporting
confidence: 55%
“…Because of the mutagenic nature of bacterial DNA, the rapid multiplication of bacterial cells, and the constant transformation of bacterial cells due to plasmid exchange and uptake, pathogenic bacteria continue to develop antimicrobial resistance, thus rendering certain antibiotics useless. An increased number of pathogens have also developed resistance [1,2] to multiple antibiotics (Multiple Drug Resistance), threatening to develop complete immunity against all antimicrobial agents and therefore be untreatable. Thus, the search for novel antimicrobial agents is of the utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of antibiotics there has been tremendous increase in the resistance of diverse bacterial pathogens (6,11). This shift in susceptibility greatly affects our ability to successfully treat patients empirically.…”
Section: Introductionmentioning
confidence: 99%